Information and Communication Technologies in Tourism 2015 2014
DOI: 10.1007/978-3-319-14343-9_37
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technologies Effects on Travel Behaviours and Experiences: A Preliminary Analysis

Abstract: The increased opportunity for tourists to be connected to the Internet during the trip, the development of social media, as well as advances in mobile technologies have profoundly affected travel experiences and behaviours. Travel stages (pre-trip, during-trip and post-trip) can overlap with a repositioning of some activities from the pre-trip and post-trip stages to the during-trip step. Therefore, the consumption of travel services becomes particularly important to be managed by travel operators, considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Some respondents even admitted that, during their travels, they sometimes become even more active than usual on social media. This also supports Minazzi and Mauri's (2015) claim that memorable travel experiences can increase the amount and variety of content that travellers' publish on social media.…”
Section: Openness To Usagesupporting
confidence: 71%
See 3 more Smart Citations
“…Some respondents even admitted that, during their travels, they sometimes become even more active than usual on social media. This also supports Minazzi and Mauri's (2015) claim that memorable travel experiences can increase the amount and variety of content that travellers' publish on social media.…”
Section: Openness To Usagesupporting
confidence: 71%
“…Memorable travel experiences increase the likelihood and the variety of content that travellers are willing to publish on social media (Minazzi and Mauri 2015). As social posts start to become a new form of postcards, the reaction of other users to the content uploaded can shape the travel experience of the uploader.…”
Section: Connectivity and Technology Enhanced Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact using a personal mobile device for online purposes during trips is seen by many travellers as important [10]. Minazzi and Mauri [14] point out that the use of mobile devices and applications affect the travel experience in different stages of the traveller life cycle. On the other hand Pesonen et al [17] found that Finnish seniors seldom use their mobile devices to connect to the Internet during trips.…”
Section: Online Activities and Older Travellersmentioning
confidence: 99%